Foraminiferal Distribution in the Central and Western Parts of the Late Pleistocene Champlain Sea Basin, Eastern Canada - Guilbault, Jean-Pierre (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1989)
ABSTRACTMarine sediments from the late-glacial Champlain Sea have been sampled at 20 localities representing the deeper part of the basin, between Ottawa and the Rivière St-François, Québec. Foraminiferal assemblages have been extracted and a sequence of three deep water and two shallow water ecozones recognized. The lowermost zone (A) is characterized by Cassidulina reniforme, Islandiella helenae and I. norcrossi and represents a paleosalinity of 25 to 30%o. The overlying zone B is dominated by Elphidium excavatum. It represents salinities decreasing from 25 to as low as 10%o. The uppermost zone (C) contains only a sparse assemblage of a morphotype of E. excavatum. If suggests a paleosalinity of no more than 10%o. A mostly unfossiliferous silt and clay layer of variable thickness (post-C) occurs above zone C. It is probably lacustrine. Below zone A and above the Late Wisconsinan till there is a pre-A interval whose variable assemblages represent hyposaline environments east of Montréal, predominantly lacustrine conditions west of Montréal and alternating hyposaline/ lacustrine environments near and south of Montréal. Bottom water temperatures were probably "Arctic" (within a few degrees of 0°) from the pre-A interval up to zone B inclusively. The data from zone C are too poor to estimate temperatures. The shallow water zones indicate environments with high (zone EH) or low (zone EA) salinities but of shallower depths than the deep water zones. The existence of two sequences is interpreted as the result of (probably seasonal) water stratification. The data does not allow to determine the depth of the limit between the shallow and deep waters.